2016
DOI: 10.1109/tccn.2016.2584080
|View full text |Cite
|
Sign up to set email alerts
|

Trust-Aware Consensus-Inspired Distributed Cooperative Spectrum Sensing for Cognitive Radio Ad Hoc Networks

Abstract: Cooperation among cognitive radios for spectrum sensing is deemed essential for environments with deep shadows. In this paper, we study cooperative spectrum sensing for cognitive radio ad hoc networks where there is no fusion center to aggregate the information from various secondary users. We propose a novel consensus-inspired cooperative sensing scheme based on linear iterations that is fully distributed and low-cost. In addition, the trade-offs on the number of consensus iterations are explored for scenario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Most of the research activities for mitigating SSDF attack mainly focussed on infrastructure‐based CRN, where a base station (aka , FC) makes the final sensing decision. However, the same study is still at an infant stage for infrastructure‐less CRN with few works found in other studies . Most of the literature in infrastructure‐less CRN adopted consensus algorithms for resisting SSDF attack.…”
Section: Related Workmentioning
confidence: 97%
See 2 more Smart Citations
“…Most of the research activities for mitigating SSDF attack mainly focussed on infrastructure‐based CRN, where a base station (aka , FC) makes the final sensing decision. However, the same study is still at an infant stage for infrastructure‐less CRN with few works found in other studies . Most of the literature in infrastructure‐less CRN adopted consensus algorithms for resisting SSDF attack.…”
Section: Related Workmentioning
confidence: 97%
“…Trust‐based literatures, which used consensus algorithm for countering SSDF attack are found in infrastructure‐less CRN . Bhattacharjee et al proposed a trust‐based monitoring mechanism to counter against SSDF attack in ad hoc CRNs.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have recently considered an attack model known as SSDF [32][33][34], which is a fatal threat to CSS. There are several typical attack patterns under the SSDF model, which are known as always opposite (AO), always busy (AB), always free (AF), and random disguising.…”
Section: Problem Formulationmentioning
confidence: 99%
“…This technique requires only the knowledge of the noise and using the Anderson‐Darling test . Furthermore, in the work of Vosoughi et al, a trust‐aware consensus was applied in the DCSS using gossip algorithm. In the work of Soatti et al, a technique named weighted AC accuracy exchange (WAC‐AE) was proposed to solve the localisation problem in networks equipped with several fixed nodes ensuring similar performance to the WAC and optimal ML but with fast convergence.…”
Section: Introductionmentioning
confidence: 99%